Taxonomical notes on the genus Chaetomitrium (Hookeriaceae, Musci) of Borneo - Hiroyuki Akiyama; Monica Suleiman (2001)
Taxonomical notes on the species of Chaetomitrium (Hookeriaceae, Musci) os the Borneo Island were provided, along with the reports of our own specimens from the island. Two new species, Chaetomitrium darnaedii H. Akiy. From East Kalimantan and C. maryatii H. Akiy. & M. Suleiman from Sabah were described. Chaetomitrium everetii Mitt. Ex Dix. and C. cucullatum Dix. Are newly reduced to synonyms of C. orthorrhynchum (Dozy & Molk.) Bosch & Sande Lac. and C. leptopoma (Schwaegr.) Bosch & Sande Lac. Respectively. Chaetomitrium elmeri Broth. Was firstly reported from the Borneo. Keys to the twelve species were also presented.